MODEL SUPERVISI AKADEMIK DI MADRASAH ALIYAH KOTA SUNGAI PENUH - Anggi Saputra; Hasnawati Hasnawati; Usdarisman Usdarisman (PRODU: Prokurasi Edukasi Jurnal Manajemen Pendidikan Islam, 2022)
This paper aims to determine the implementation of academic supervision at the Madrasah Aliyah in Sungai Penuh City. The method used is a survey method. The findings showed that the implementation of academic supervision at the Madrasah Aliyah in Sungai Penuh City was categorized as low. This is because academic supervision does not channel government regulations to declare and improve the quality of education through improving teacher performance in the school environment, especially in madrasas. Operationally, the supervisor's work only evaluates the teacher's performance. During the COVID-19 pandemic, the implementation of academic supervision was increasingly not carried out properly because they used the 47.5% zoom meeting application in supervisor activities.